Rethinking occupational welfare policies in long-term care organisations during the COVID19 pandemic: An organisational ethics approach - Mion, Giorgio; Bonfanti, Angelo; Simeoni, Francesca; Loza Adaui, Cristian Rolando (International Journal of Managerial and Financial Accounting, 2021)
Non-profit organisations, in particular long-term care organisations, have faced several challenges arising from the COVID-19 pandemic. Long-term care organisations have had to meet these challenges by relying on their core ethical values and human capital. This paper examines the occupational welfare policies adopted by a long-term care organisation during the pandemic and the individual, managerial, organisational and societal effects of these policies from an organisational ethics perspective. The study explores the case of a non-profit organisation - Fondazione Monsignor Alessandro Marangoni - that adopted occupational welfare policies, enabling it to manage the early COVID-19 outbreak without negative consequences. The findings show that organisational ethics are embedded into occupational welfare policies and demonstrate their role for the welfare society in times of crisis.
Keywords: Long-term care; non-profit organisations; occupational welfare policies; residential services for elderly; intrinsic motivations; value-based organisations; welfare service management; organisational ethics; Covid-19 pandemic.